2021
DOI: 10.1186/s40658-021-00371-w
|View full text |Cite
|
Sign up to set email alerts
|

Q-Bot: automatic DICOM metadata monitoring for the next level of quality management in nuclear medicine

Abstract: Background Regular and precise inspection of the realization of the local nuclear medicine standard operation procedures (SOPs) is very complex and time-consuming, especially when large amount of patient data is obtained from a wide scale of different scan procedures on a daily basis. DICOM metadata comprise a complete set of data related to the patient and the imaging procedure, and consequently all information necessary to evaluate the compliance with the actual SOP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…This information can be used in different ways to assess the quality of imaging and the radiation doses received by patients. [3][4][5][6] As part of the TMIST QC program, images from trial participants are de-identified, stripped of the actual breast image and the header of each image is captured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This information can be used in different ways to assess the quality of imaging and the radiation doses received by patients. [3][4][5][6] As part of the TMIST QC program, images from trial participants are de-identified, stripped of the actual breast image and the header of each image is captured.…”
Section: Introductionmentioning
confidence: 99%
“…Each mammographic and tomosynthesis image contains a header in which information (“metadata”) on many parameters of the image acquisition are recorded. This information can be used in different ways to assess the quality of imaging and the radiation doses received by patients 3–6 . As part of the TMIST QC program, images from trial participants are de‐identified, stripped of the actual breast image and the header of each image is captured.…”
Section: Introductionmentioning
confidence: 99%